1981
DOI: 10.1152/ajpheart.1981.240.4.h441
|View full text |Cite
|
Sign up to set email alerts
|

Relaxing effect of pharmacologic interventions increasing cAMP in rat heart

Abstract: The relationship between cAMP and relaxation was studied in the isolated rat heart beating at constant rate and perfused at constant coronary flow. After treatment during 1 min with different positive inotropic interventions, cyclic nucleotide levels (cAMP and cGMP) and cAMP-dependent protein kinase activity were determined in heart homogenates. Glucagon, norepinephrine, and isoproterenol increased cAMP from 0.503 +/- 0.025 pmol/mg wet wt to 1.051 +/- 0.099, 0.900 +/- 0.064, and 0.982 +/- 0.138, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…23,000 was localized to a band of Mr betwen 11,000 and 12,000 (Fig. As already described (5,19,24), ISO produced a relaxant effect, evidenced by the proportional greater increase in -T than in +~i" (i.e. This behavior is typical of phospholamban, and the two proteins of different molecular weights are thought to be the high and low molecular forms of this protein (17,23).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…23,000 was localized to a band of Mr betwen 11,000 and 12,000 (Fig. As already described (5,19,24), ISO produced a relaxant effect, evidenced by the proportional greater increase in -T than in +~i" (i.e. This behavior is typical of phospholamban, and the two proteins of different molecular weights are thought to be the high and low molecular forms of this protein (17,23).…”
Section: Discussionmentioning
confidence: 57%
“…However, differences in relaxation can occur despite identical changes in contraction (5,19,24), suggesting that the two processes can be modified separately: experiments from our own laboratory (5,24) have shown that the ratio between both maximal velocities (+T/-~i') can be decreased following pharmacological interventions which increase cAMP and cAMPdependent protein kinase activity. Whenever maximal velocity of contraction increases, maximal velocity of relaxation also increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High speed records (0.25 s/frame) were used in order to measure peak developed force (F) and, on its first derivative (dF/ dt), maximal velocity of contraction (+dF/ dt max ) and maximal velocity of relaxation (-dF/dt max ). The +dF/dt max /-dF/dt max ratio was calculated to evaluate the relative effect of each intervention on velocities of contraction and relaxation, with its decrease being considered evidence of a positive lusitropic (or relaxant) effect and its increase being considered evidence of a negative lusitropic (or antirelaxant) effect (7,8).…”
Section: Isolated Rat Atrium Preparationmentioning
confidence: 99%
“…In mammalian heart, the positive inotropic effect of ct and [3-adrenergic agents is coupled with different changes in relaxation. Whereas 13-adrenergic agonists cause a relaxant (positive lusitropic) effect [1][2][3], a-adrenergic stimulation evokes a negative lusitropic action [4]. Although both in-*Fellow of CONICET terventions appear to increase the amplitude ofcytosolic Ca 2 § transient, they have opposite effect on myofilament responsiveness to Ca :+-.…”
Section: Introductionmentioning
confidence: 99%